Cheating in mind games: The subtlety of rules matters - Jiang, Ting (Journal of economic behavior & organization, 2013)
•Cheating is invisible in the mind game.•I compare cheating behavior using two variants of the “mind game”.•The only difference between the variants rests on the ordering of the instructed steps.•The ordering not only affects the extent of cheating, but also leads to distinct behavioral patterns including decision time. This paper employs two variants of the “mind game” to show how a subtle variation in the game's rules affects cheating. In both variants of the game, cheating is invisible because subjects make their choices purely in their minds. The only difference stems from the ordering of steps that subjects are instructed to follow when playing the game. The order of play has a significant impact on cheating behavior, even though the rules cannot be enforced.